Disponibilidad y explotación de materias primas líticas en la Costa de Norpatagonia (Argentina) : un enfoque regional - Alberti, Jimena, (South American archaeology series ;, 2016)
This work studies the use of lithic raw materials on the coast of the San Matías gulf (Río Negro, Argentina) during the middle and late Holocene.